Judge Barry S. Schermer: A Teacher of Law and of Life - Emily K. Cohen (Washington University Journal of Law & Policy, 2017)
This Article reflects on lessons learned from Judge Barry Schermer from one of his current law clerks. Cohen recalls her experiences with Judge Schermer while a student at Washington University School of Law, and how his teaching styles influenced her to pursue bankruptcy law. The author recounts many of the legal skills emphasized by Judge Schermer’s collaborative and team-centered environment, but as well as the personable aspects of his practice that maintain his well-regarded reputation in the legal community.
Keywords: Judge Schermer; Law School; Clerkship; Federal Clerkship; Mentorship